Analysis Of Promotion And Service Quality On Customer Loyalty At Pln Tanjung Pura Ulp Mediated By Customer Satisfaction In The Use Of Pln Mobile Application - Taufik Harijanto; Toyib Daulay; Desy Astuti; Elfitra Desy Surya; Mesra B (Yayasan Multidimensi Kreatif, 2023)
This research investigates the impact of promotion, service quality, and emotional bonding on customer loyalty at PLN Tanjung Pura ULP, mediated by customer satisfaction through the PLN Mobile application. Utilizing a quantitative approach with structural equation modeling, the study reveals that promotion and service quality significantly influence customer satisfaction, subsequently affecting customer loyalty. The findings emphasize the importance of effective promotional strategies, high service quality, and emotional connections in enhancing customer satisfaction and loyalty. Recommendations include promoting PLN Mobile adoption through step-by-step guidance, improving service quality through employee training and customer feedback, and fostering emotional bonds with special offers for loyal users. Overall, the study highlights the interconnected dynamics shaping customer loyalty in the context of PLN Mobile usage.